2017
DOI: 10.3390/rel8070121
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Gender Ideologies among Working-Age U.S. Latinas/os

Abstract: Numerous studies have documented religious variations in gender ideology in the United States. Despite growth, diversification, and religious ferment among Latinas/os, few have investigated this topic within the Latina/o population. Drawing on insights from gender theory and prior empirical research, we develop several hypotheses regarding the links between religious affiliation, belief, and practice and three distinct domains of traditionalist gender ideology (respective beliefs in female domesticity, gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 59 publications
1
18
1
Order By: Relevance
“…Women still earn only 80 percent of what men earn for full‐time work and are less likely to hold managerial or supervisory positions, and when they do, their positions carry less authority. Further, even when both partners earn wages, women do twice as much housework and child care (Mayo & Resnick, ; Piña‐Watson, Lorenzo‐Blanco, Dornhecker, & Nagoshi, ; Ruiz, Bartkowski, Ellison, Acevedo, & Xu, ). In addition, studies have demonstrated that women perceived more gender discrimination than men against their group, which is consistent with socioeconomic disparities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Women still earn only 80 percent of what men earn for full‐time work and are less likely to hold managerial or supervisory positions, and when they do, their positions carry less authority. Further, even when both partners earn wages, women do twice as much housework and child care (Mayo & Resnick, ; Piña‐Watson, Lorenzo‐Blanco, Dornhecker, & Nagoshi, ; Ruiz, Bartkowski, Ellison, Acevedo, & Xu, ). In addition, studies have demonstrated that women perceived more gender discrimination than men against their group, which is consistent with socioeconomic disparities.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, Latinos hold more conservative attitudes regarding gender roles when compared to Whites (Bejarano, Manzano, & Montoya, 2011). For instance, traditional gender roles such as marianismo and machismo are endorsed in the Latino culture (Miville et al, 2017;Ruiz et al, 2017). Men usually hold an authoritarian position; they strive to maintain respect; and have the perception that they are stronger, more reliable, and more intelligent than women (Gowan & Treviño, 1998;Harris & Firestone, 1998;Mayo & Resnick, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative studies of religion and gender in the United States have generally concluded that the religiously affiliated have less egalitarian attitudes than the non-affiliated and that Conservative Protestants are the least egalitarian (see Fan and Marini (2000) for a review). Among Latinas/os, Ruiz et al (2017) found no significant difference between Catholics and the religiously unaffiliated, but they did find Conservative Protestants to be less egalitarian.…”
Section: The Formation Of Gender Attitudesmentioning
confidence: 78%
“…First, it affects labor force participation and earnings (see Rodríguez and Pillai (2017) for a review). Women who understand the female role as being mainly centered in the domestic realm are less likely to participate in paid employment (Thornton et al 1983), with some believing that women's outside employment can have harmful effects on children (Ruiz et al 2017). Alternatively, women with more egalitarian attitudes work more hours and have higher hourly earnings than those with less egalitarian attitudes (Corrigall and Konrad 2007).…”
Section: The Importance Of Gender Attitudesmentioning
confidence: 99%